Putting the Puzzle Together To Get the Whole Picture: Molecular Basis of the Affinity of Two Steroid Derivatives to Acetylcholinesterase - Richmond, Victoria (2023)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder that has no cure because its etiology is still unknown, and its main treatment is the administration of acetylcholinesterase (AChE) inhibitors. The study of the mechanism of action of this family of compounds is critical for the design of new more potent and specific inhibitors. In this work, we study the molecular basis of an uncompetitive inhibitor (compound 1, 2β, 3α-dihydroxy-5α-cholestan-6-one disulfate), which we have proved to be a peripheral anionic site (PAS)-binding AChE inhibitor. The pipeline designed in this work is key to the development of other PAS inhibitors that not only inhibit the esterase action of the enzyme but could also modulate the non-cholinergic functions of AChE linked to the process of amylogenesis. Our studies showed that 1 inhibits the enzyme not simply by blocking the main gate but by an allosteric mechanism. A detailed and careful analysis of the ligand binding position and the protein dynamics, particularly regarding their secondary gates and active site, was necessary to conclude this. The same analysis was executed with an inactive analogue (compound 2, 2β, 3α-dihydroxy-5α-cholestan-6-one). Our first computational results showed no differences in affinity to AChE between both steroids, making further analysis necessary. This work highlights the variables to be considered and develops a refined methodology, for the successful design of new potent dual-action drugs for AD, particularly PAS inhibitors, an attractive strategy to combat AD.